Method study of hot working conditions - Williams, J. A. C. (College of Aeronautics, 1956)
i. Introduction and. Historical Note A convenient dichotomy of the technology of Work Study in everyday use1 is (a)Method Study (b) Work measurement This applies to most current work conditions and techniques although the work sampling techniques of ratio delay and memomotion do not fill conveniently into either. The usual chart methods and photographic techniques used in. method study stem from the practice of the Gilbreths so th4t same practitioners equate method study with motion study 4. Such a view would necessarily restrict method study to movement at normal temperatures and leave outside the study of work conditions which are the interest of the ergonomist. In everyday practice no rigid division of the study of industrial work situations can be made and an eclectic approach is required even in the big organisations employing specialists. The term 'ergonomist' is used in the sense that the technician concerned has a wider interest and training than that needed for motion study, Such D. use stems back to P.N.. Taylor Whose use3 of the term Time Study (as opposed to the modern 'time study') implied (a) the study of work and experimentation to develop the best method of performing a job which was then standardised (b) the division of a work cycle into elements, the timing by stopwatch of these when performed. by a selected, suitably trained and highly motivated worker. The addition of allowances for rest, necessary delays etc. and the establishment of a time to be used as a basis for planning anal control and the setting up of a wage incentive scheme. (c) The analysis of all such established times so that a system of synthetic times can be used for forward planning.